The hill we climb an inaugural poem for the country - Gorman, Amanda (New York Viking, 2021)
On January 20, 2021, Amanda Gorman became the sixth and youngest poet, at age twenty-two, to deliver a poetry reading at a presidential inauguration. Her inaugural poem, "The Hill We Climb," is now available to cherish in this special edition
Keywords: Biden, Joseph R., Jr.--Inaugurations--Poetry.